Commercialization of Medical Services as a Business Practice: A Legal Analysis of Conflicts of Interest and Patient Protection in Indonesia - Aris Prio Agus Santoso (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
There is a growing gap between the normative regulation of medical services, which is oriented toward patient safety, and the reality of commercialized practice driven by economic interests. This condition creates conflicts of interest and weakens legal protection for patients. This study aims to analyze the legal framework governing the commercialization of medical services and examine its implications for patient protection in order to realize a healthcare system that is fair, professional, and patient-oriented. The research method used is a normative legal approach that analyzes legal norms, principles, and rules. The analysis is conducted qualitatively to produce theoretical understanding and comprehensive legal argumentation regarding the relationship between business practices in medical services and the legal responsibilities of medical personnel. The findings show that Indonesia’s legal framework for the commercialization of medical services recognizes the economic aspects of medical professionals and healthcare facilities, but it is still constrained by ethical principles, professionalism, and patient protection, resulting in a normative dualism between economic orientation and humanitarian values. In practice, this dualism has not been harmoniously implemented due to the persistent gap between norms and implementation. This condition weakens patient protection, increases the risk of over-treatment, creates information asymmetry, and shifts the doctor–patient relationship into a transactional one that may trigger medical disputes and service injustice. Therefore, stronger regulatory enforcement, clearer separation between medical and business functions, service transparency, strengthened ethical supervision, and reform of medical legal culture are required to achieve a balanced healthcare system that fairly integrates economic interests with patient protection and prioritizes patient safety.